2020
DOI: 10.1073/pnas.2010146117
|View full text |Cite
|
Sign up to set email alerts
|

Broad host range of SARS-CoV-2 predicted by comparative and structural analysis of ACE2 in vertebrates

Abstract: The novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of COVID-19. The main receptor of SARS-CoV-2, angiotensin I converting enzyme 2 (ACE2), is now undergoing extensive scrutiny to understand the routes of transmission and sensitivity in different species. Here, we utilized a unique dataset of ACE2 sequences from 410 vertebrate species, including 252 mammals, to study the conservation of ACE2 and its potential to be used as a receptor by SARS-CoV-2. We designed a five… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
641
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 580 publications
(738 citation statements)
references
References 100 publications
(175 reference statements)
38
641
1
8
Order By: Relevance
“…As shown in previous studies, and supported by experimental data, many primates are predicted to be at high risk 19,41,42 . In agricultural settings, camels, cows, sheep, goats and horses also have relatively low ΔΔG values, suggesting comparable binding affinities to humans, in agreement with experimental data 20,21,48 .…”
supporting
confidence: 71%
See 2 more Smart Citations
“…As shown in previous studies, and supported by experimental data, many primates are predicted to be at high risk 19,41,42 . In agricultural settings, camels, cows, sheep, goats and horses also have relatively low ΔΔG values, suggesting comparable binding affinities to humans, in agreement with experimental data 20,21,48 .…”
supporting
confidence: 71%
“…However, to our knowledge there have been few studies of relative changes in the energies of the S-protein:ACE2 complex 43 . A number of recent studies 20,21,42 have suggested that, due to high conservation of ACE2, some animals are vulnerable to infection by SARS-CoV-2. Concerningly, these animals could, in theory, serve as reservoirs of the virus, increasing the risk of future zoonotic events, though transmission rates across species are currently not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies of ACE2 sequence alignment with limited structural modeling have suggested that pigs are susceptible to infection, 52 and that hamsters and house cats are in an intermediate-risk group. 53 Recent experimental work with direct inoculation, however, has demonstrated that pigs are non-susceptible, 7 and that house cats and Golden Syrian hamsters are susceptible. 5,7 We identified key residues on which to build a susceptibility score that closely matches experimentally verified in vivo susceptibility, including predicting an intermediate susceptibility of the pig and higher susceptibility of house cats and Golden Syrian hamsters.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data relating to treatment of both non-CNS and CNS FIP with antiviral drugs may have relevance to specific aspects of ongoing trials in SARS-CoV-2 patients. Interestingly, domestic and big cats are susceptible to SARS-CoV-2 infection, consistent with expression of ACE2 viral receptor in these species (87,88), although associated clinical CNS disease has not been reported (89,90).…”
Section: Treatmentmentioning
confidence: 55%